2020
DOI: 10.1007/s00520-020-05695-4
|View full text |Cite
|
Sign up to set email alerts
|

Patient outcomes, patient experiences and process indicators associated with the routine use of patient-reported outcome measures (PROMs) in cancer care: a systematic review

Abstract: Purpose In current cancer care, there is a growing debate about the value of using patient-reported outcome measures (PROMs) in daily clinical follow-up. A systematic review of the literature was conducted to assess the evidence of the effectiveness of the routine use of PROMs in daily cancer care in terms of patient outcomes, patient experiences and process indicators and to identify the effect of giving feedback about PROM findings to patients and/or health care professionals (HCPs). Methods A systematic sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
80
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 50 publications
3
80
0
3
Order By: Relevance
“…Several oncological and non-oncological studies reported that the use of PROMs is associated with improved patientphysician communication, higher patient satisfaction, and improved symptom control. Results were most pronounced when feedback was provided to patient and healthcare professional (HCP) regarding the findings of the PROM [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Several oncological and non-oncological studies reported that the use of PROMs is associated with improved patientphysician communication, higher patient satisfaction, and improved symptom control. Results were most pronounced when feedback was provided to patient and healthcare professional (HCP) regarding the findings of the PROM [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The body of evidence regarding the benefit of using PROMs in a patient-centred context to improve patient outcomes is indisputable, with examples such as better communication between health care providers and patients, raised awareness and better management of symptoms, extended survival time, advising treatment decisions, and informing service delivery [ 2 , 18 , 19 , 20 , 21 , 22 , 23 ]. However, the use of PROMs to elicit patients’ views is not as widespread nor as systematic as necessary for provision of good quality care, not in general oncology, nor in palliative care [ 22 , 24 , 25 , 26 ]. In fact, reviews and meta-analyses show that 38% of cancer patients report moderate to severe pain (≥5 on 0–10 scales) and that one-third does not receive adequate pain medication [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies with a qualitative angle are still few and in most cases have insufficient power. This makes it difficult to carry out more authoritative systematic reviews [ 15 , 16 ]. Given the fact that oral mucositis a continuum of gastro-intestinal mucositis is a dose /schedule modifying complication of chemotherapy [ 17 ], there is a need to identify areas of interventions that can reduce the suffering among patients undergoing cancer treatment.…”
Section: Introductionmentioning
confidence: 99%